Psychological Dimensions of Pain: The Biopsychosocial Model and the Fear-Avoidance Cycle - Nurvita Sari Musdiani Silalahi (Budapest International Research in Exact Sciences (BirEx) Journal, 2026)
The experience of pain cannot be explained solely through biological mechanisms. Psychological and social factors significantly influence how individuals perceive and respond to pain. This article examines the psychological dimension of pain through the biopsychosocial model and the fear-avoidance framework. The biopsychosocial model, first proposed by George L. Engel, emphasizes the interaction of biological, psychological, and social factors in shaping health outcomes. Additionally, the fear-avoidance model explains how catastrophic interpretations of pain can lead to avoidance behavior, disability, and chronic pain conditions. Drawing on contemporary research, this article demonstrates that psychological processes such as beliefs, expectations, and emotional responses play a central role in pain persistence. The findings highlight the importance of addressing psychological and social dimensions in pain management strategies.